Three-Dimensional Atomic Imaging of Colloidal Core–Shell Nanocrystals - Bals, Sara; Casavola, Marianna; van Huis, Marijn A; Van Aert, Sandra; Batenburg, K. Joost; Van Tendeloo, Gustaaf; Vanmaekelbergh, Daniël (Nano letters, 2011)
Colloidal core–shell semiconductor nanocrystals form an important class of optoelectronic materials, in which the exciton wave functions can be tailored by the atomic configuration of the core, the interfacial layers, and the shell. Here, we provide a trustful 3D characterization at the atomic scale of a free-standing PbSe(core)–CdSe(shell) nanocrystal by combining electron microscopy and discrete tomography. Our results yield unique insights for understanding the process of cation exchange, which is widely employed in the synthesis of core–shell nanocrystals. The study that we present is generally applicable to the broad range of colloidal heteronanocrystals that currently emerge as a new class of materials with technological importance.